Cross-cultural adaptation and content validity of an instrument to determine palliative needs in Colombia - Celis Moreno, Jhonatan Sebastian; Vargas Pelaez, Maribel (Horizonte Sanitario, 2022)
Objetive: Carry out the cross-cultural adaptation and to evaluate the validity of the content into Spanish of the NECPAL instrument of CCOMS© for patients admitted to the ICU for use in Colombia. Materials and methods: Methodological study of cross-cultural adaptation and content validity. Data collection was carried out from June to November 2020. The sample consisted of 12 specialists. The NECPAL instrument was evaluated determining the transcendence and the items, identifying the clarity, pertinence and relevance. To evaluate each item, a 3-level Likert-type scale was used. Content validity was assessed using Lawshe’s Content Validity Index (CVI) Results: It was determined that the NECPAL instrument is suitable for use in the Colombian context. Adjustments were made to improve your performance. The IVC of the NECPAL instrument was 0.96. Conclusions: The NECPAL instrument in its Colombian Spanish version is appropriate to determine palliative needs in patients hospitalized in the ICU. Key words: Palliative care; Needs assessment; Critical Care; Chronic disease; Validation Study